SOLID FUEL FROM EMPTY FRUIT BUNCH FIBER AND WASTE PAPERS PART 1: HEAT RELEASED FROM CUMBUSTION TEST - YAAKOB, MOHD YUHAZRI; HASOLOAN, HAERY IAN PIETER (Global Engineers and Technologists Review, 2012)
This research discussed on the results obtained for each sample that have been conducted to the solid fuel briquettes made of empty fruit bunch fiber and waste papers from view of heat released during combustion test. The results shows tremendous amount of energy can be generated from these biomass compositions. The energy can easily harness to generate heat and electricity for many productive operations. Hence, the possibility result in this research is the development of solid fuel briquette by mixing the empty fruit bunch with a waste paper can be one sources of fuel energy. From the combustion analysis shows sample briquette with ratio 60:40 has given a highest value of heat released which is 162.77 kJ, whereas sample with ratio 40:60 has good burning time.